The Role of Opinion Polling data in Electoral Campaigns in Malawi: Rethinking Political Strategy in Data-Poor Electoral Contexts - Kalanda, Boniface Francis (Advances in Social Sciences Research Journal, 2025)
This paper examines how weak or absent opinion polling systems undermine electoral competitiveness and strategic decision-making among political parties in Malawi. Using the 2025 general elections as a case study, the analysis explores how the Malawi Congress Party (MCP) and other political actors relied on anecdotal evidence and informal networks rather than systematic voter data to guide campaign strategy. Drawing on interviews, campaign documents, and comparative experiences from data-rich electoral environments, the paper argues that the absence of credible, frequent, and scientifically grounded opinion polling limited parties’ ability to identify swing constituencies, adapt messages, and respond to shifting voter sentiments. The analysis situates this challenge within broader debates on the role of information in democratic competition, showing that data-poor contexts constrain both campaign efficiency and democratic responsiveness. It concludes that strengthening independent polling institutions and fostering a culture of evidence-based political communication are essential for parties seeking electoral success and for the consolidation of democracy in Malawi and similar emerging democracies.